Beak trimming and stocking densities for laying and performance traits and behavioral patterns in Japanese quails - Paz Aguiar, Daniela (2021)
The present experiment was conducted to evaluate the productive performance, egg quality and behavioral patterns of Japanese quails (Coturnix coturnix japonica) with and without beak trimming submitted to two stocking densities. The study was conducted for 84 days. In total, 196 Japanese quails were randomly allocated to a 2 x 2 factorial scheme: submitted or not to beak trimming procedure and low (237.5 cm²/bird) and high stocking density (316.7 cm/bird) and its interaction. Eight replicates per treatment were used, totaling 32 experimental units. Collected data were submitted to analysis of variance and, means of parametric data were compared by Tukey test (p<0.05); otherwise non-parametric analysis of variance were applied for non-parametric data of quail behavior. Lower feed intake was observed in the high stocking density group (p<0.05) but did not affect other parameters (p>0.05). There was no interaction (p>0.05) between beak trimming and stocking density over performance and egg quality. Quails without beak trimming housed in higher density showed more aggressiveness and stress. Egg quality as well as performance parameters of Japanese quails are not affected by applying 316.7 cm2/bird density.